PERTANGGUNGJAWABAN NOTARIS TERHADAP PEMBATALAN AKTA PERJANJIAN PERKAWINAN BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Elisa Safira; Abdul Salam (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2022)
Abstract In practice, the marriage agreement deed made by a notary can be cancelled by the court. The cancellation causes losses for the party who made it. So it becomes a problem how the notary's responsibility for the cancellation of the marriage agreement deed made in the form of a notary deed carried out by the court. This study aims to analyse the notary's responsibility for cancelling the marriage agreement deed made by the court. The research method used is normative juridical research using a statutory approach and a case approach. The results showed that the notary's responsibility for the marriage agreement deed was cancelled by the court's decision, especially in case number 598 PK/PDT/2016, providing information because the case was included in the administrative area.Furthermore, in the Law on Notary Positions, the notary's responsibility to the deed he makes is that the notary's responsibility is charged to his position. So the result is that the marriage agreement in case Number 598 PK/PDT/2016 is null and void because it does not meet the requirements in Article 29 paragraph (1) of the Marriage Law Article 147 of the Civil Code, namely the marriage agreement, must be made before or when the marriage takes place and is made in a notary deed and ratified by the marriage registrar. Concerning the cancellation of the marriage agreement, it returns to its original state as did not occur in the previous agreement, namely the merger of assets during the marriage and its distribution. Notaries, as public officials, can be held accountable for authentic deeds, resulting in null and void that they make based on the distribution of responsibilities. In this case, the notary's responsibility is borne by the position.